Some Records of Extreme Longevity Of Seeds of Indian Forest Plants - Dent, T. V. (Indian Forester, 1942)
Germination tests were carried out on old dated seed selected from exhibition cases in the museums of the Forest Research Institute at Dehra Dun. The 64 samples examined represented 52 selected species of native, naturalised or cultivated Indian plants, most of them forest trees; the seed ages varied from 7 to 62 years, the majority being above 20 years.The oldest sample which germinated was a single seed of Casalpinia digyna, aged 41 years, which has produced a healthy flourishing plant; 24-year-old seed of the same species also germinated. Freely other long-lived seeds of the natural order Leguminosae were Acacia farnesiana (31 years), Cassia fistula (31 years), Albi ia lebbek (30 years), Albissia odoratissima (27 years), Dichrostachys cinerca (26 years), Acacia dealbata (23 years), Acacia decurrens (23 years) and Leucana glauca (23 years). Long-lived seed were also found in the natural order Malvaceae, three out of the four species examined given positive results, namely, Hibiscus macrophyllus (24 years), Ochroma lagopus (24 years, seed from America) and Abutilon indicum (17 years). Three seeds of Nelumbium speciosum (Nelumbiaceae) from a herbarium sheet over 62 years old failed to germinate, but four seeds of the same species collected in 1935, 7 years ago, germinated with great vigour. Nelumbium is an aquatic herb, not a forest-plant, but it is reputed to have very long-lived seeds and carries a special interest on this account. The imminence of his transfer from Dehra Dun has for the present prevented the writer from proceeding fUrther with these preliminary investigations into the longevity of Indian seeds.